2023
DOI: 10.3390/biology12030368
|View full text |Cite
|
Sign up to set email alerts
|

Marine Plankton during the Polar Night: Environmental Predictors of Spatial Variability

Abstract: We studied the spatial patterns of the planktonic ecosystems at two Arctic sites strongly affected by Atlantic Inflow (FS, the Fram Strait; and BS, the Barents Sea). A high degree of similarity in the bacterial abundance (mean: 3.1 × 105 cells mL−1 in FS vs. 3.5 × 105 cells mL−1 in BS) was found, while other plankton characteristics were different. Bacterial biomass reached a maximum in BS (3.2–7.9 mgC m−3), while viral abundances tended to be higher in FS (2.0–5.7 × 106 particles mL−1). Larger bacterial cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 96 publications
1
1
0
Order By: Relevance
“…Therefore, when calculating total prokaryotic biomass, we are assuming that the relationship between cell-specific carbon and temperature is similar across both depth and latitude in colder waters. Cell biovolumes in polar waters might not differ substantially from our Malaspina dataset 31 , and latitudinal increases in cell-specific carbon biomass have previously been reported 32 , which would support our assumption here. Changes in prokaryote prevalence in surface waters were relatively small compared to the magnitude of variability in environmental conditions.…”
Section: Environmental Drivers Of Prokaryotic Abundance Size and Biomasssupporting
confidence: 90%
“…Therefore, when calculating total prokaryotic biomass, we are assuming that the relationship between cell-specific carbon and temperature is similar across both depth and latitude in colder waters. Cell biovolumes in polar waters might not differ substantially from our Malaspina dataset 31 , and latitudinal increases in cell-specific carbon biomass have previously been reported 32 , which would support our assumption here. Changes in prokaryote prevalence in surface waters were relatively small compared to the magnitude of variability in environmental conditions.…”
Section: Environmental Drivers Of Prokaryotic Abundance Size and Biomasssupporting
confidence: 90%
“…Ocean currents have been shown to affect the number of zooplankton moving through the Fram Strait, and found that copepods rich in carbon, like C. finmarchicus, were abundant (Basedow et al 2018). Even in winter, copepods, especially Calanus species, were still dominant in the waters around Svalbard (Dvoretsky and Dvoretsky 2020;Dvoretsky et al 2023). The influence of AW on zooplankton in Kongsfjorden varies depending on local ocean conditions, as recent research has shown (Gluchowska et al ).…”
Section: Introductionmentioning
confidence: 94%